Effect of Contact Lens Wear on Tear Film Break up Time (TBUT) among Contact Lens Users - Ammer, Rabia (Pakistan Journal of Ophthalmology, 2017)
Purpose: To determine the effect of contact lens wear on tear film break up time (TBUT) and to find out correlation between tear film break up time (TBUT) with type of contact lens wear, daily wearing time of contact lens, years of contact lens use and power of contact lens. Study Design: Cross-sectional study and convenient sampling was used. Place and Duration of Study: This study recruited the sample from Madinah Teaching Hospital Faisalabad, E Plomer Optics and Punjab Optics Lahore. The study was conducted in 4 months from 05-04-2016 to 05-08-2016. Materials and Methods: TBUT determined by using slit lamp and fluorescein strips. SPSS version 23 was used for data analysis. Inferential statistics was reported for variables. Results: A sample of 100 (67 females and 33 males) contact lens users recruited for the study. Mean age of sample was 30.10 ± 7.86 years. Mean daily wearing time of contact lens was 9.82 ± 2.19 hours/day and mean of years of contact lens use was 8.35 ± 5.81 years. 67% of 100 contact lens users had abnormal (less than 10 sec.) tear film break up time (TBUT). A significant negative correlation of TBUT was found with daily wearing time of contact lenses (r = -.251), years of contact lens use (r = -.542) and minus power of contact lens (r=-.330). No significant association of TBUT was found with type of contact lens and plus power of contact lens. Conclusions: TBUT decreases with increase in daily wearing time, years of contact lens use and high minus power of contact lens, while type of contact lens and plus power of contact did not significantly affect the TBUT. Ke Words: contact lens, tear film break up time, TBUT, tear film stability.